DLC Coatings in Oil and Gas Production - Liskiewicz, Tomasz; Al-Borno, Amal (Journal of Coating Science and Technology, 2014)
Diamond-like carbon (DLC) coatings are recognized in many sectors as a promising way of controlling wear and the corrosion performance of components. DLC coatings are well established in the automotive industry where they are applied to the moving parts of direct injection fuel systems operating under frictional conditions at high pressures and in the aggressive environment of the combustion chamber. Over the last few years, there has also been an increasing number of reports of DLC coating applications in oil and gas production contexts, including in pipes, shut-off gates and various types of valves. This paper reviews current efforts to use DLC coatings in the oil and gas sectors and analyses typical coating degradation mechanisms including wear and wear-accelerated corrosion regimes. DLC coating deposition techniques, including Physical (PVD) and Chemical Vapor Deposition (CVD) techniques, are elaborated, and the unique coating properties obtained from those two methods are assessed. Surface functionalization is discussed, including dopants (W and Si) and gradient interlayers. Finally, the outlook for future use of DLC coatings in oil and gas production is discussed.